2021
DOI: 10.3390/su13116240
|View full text |Cite
|
Sign up to set email alerts
|

Implicating Human Values for designing a Digital Government Collaborative Platform for Environmental Issues: A Value Sensitive Design Approach

Abstract: Digital technology is instrumental in designing e-government services to achieve environmental sustainability. This study aims to implicate essential human values for designing a Digital Government Collaborative Platform (DGCP), which seeks to enhance the collaboration between citizens and government officers to address environmental issues in Sri Lanka. The study adopts a value sensitive design (VSD) approach to identify human values to conceptualize the design. The results reveal 15 human values shared by ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…Despite the acknowledged relevance of digital government in relation to sustainability, research on this relationship so far has been both underwhelming and fragmented. Only a small fraction of the body of research on digital government focuses on sustainability and sustainable development (Medaglia et al, 2021;Sapraz & Han, 2019). Some of the existing empirical studies on digital government and sustainability tend to emphasize the role of specific technologies.…”
Section: An Under-researched Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the acknowledged relevance of digital government in relation to sustainability, research on this relationship so far has been both underwhelming and fragmented. Only a small fraction of the body of research on digital government focuses on sustainability and sustainable development (Medaglia et al, 2021;Sapraz & Han, 2019). Some of the existing empirical studies on digital government and sustainability tend to emphasize the role of specific technologies.…”
Section: An Under-researched Fieldmentioning
confidence: 99%
“…Existing studies, however, predominantly concentrate on governmental strategies and policy-making (Sapraz & Han, 2019). For example, digital government initiatives play a key role in promoting the reuse, repair and recycle of manufactured products in the supply chains of relevant industries, following the model of the Circular Economy (Medaglia et al, forthcoming), in line with SDG 12 (Ensure sustainable consumption and production patterns).…”
Section: An Under-researched Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used the appropriate techniques of VSD to develop DGCP. In a prior study (Sapraz and Han, 2021), 15 human values were identified (Table 2) and converted into design requirements using the values-norms-design requirements method (Van De Poel, 2013). These features are embedded and represented in the developed system (Sapraz and Han, 2022a).…”
Section: Research Backgroundmentioning
confidence: 99%
“…To facilitate collaboration between the government and the citizens to address environmental issues in Sri Lanka, a Digital Government Collaborative Platform (DGCP) is designed and developed by adopting the value-sensitive design (VSD) approach (Sapraz and Han, 2021, 2022a). A rigorous evaluation of the DGCP is required to ensure that the platform fulfills the design requirements and meets the needs of the stakeholders.…”
Section: Introductionmentioning
confidence: 99%